Pass-Through By Multiproduct Firms - André Romahn; Richard Friberg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
How does cost pass-through to prices depend on the set of products a multiproduct firm owns? Using a structural demand model for the Swedish beer market, we simulate equilibrium cost pass-through for varying counterfactual ownership patterns. We find that a firm with a larger number of products in its portfolio and a higher degree of substitutability among these products adopts a lower pass-through of costs. While the direction of results is robust, our simulations show that the muting effect on pass-through is limited when comparing pass-through by stand-alone firms to pass-through under the actual, moderately concentrated, market structure.
Keywords: L11; L13; E31; 330